2021
DOI: 10.1371/journal.pone.0258229
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic hepatitis B infection and COVID-19 outcomes: A Korean nationwide cohort study

Abstract: Background/Aims We measured the association between underlying chronic hepatitis B (CHB) and antiviral use with infection rates among patients who underwent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing. Methods In total, 204,418 patients who were tested for SARS-CoV-2 between January and June 2020 were included. For each case patient (n = 7,723) with a positive SARS-CoV-2 test, random controls (n = 46,231) were selected from the target population who had been exposed to someone with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…This is consistent with the other studies with a relatively small number of patients that HBV itself did not affect the clinical outcomes of the COVID-19 after adjusting for comorbidities. 9 11 18 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the other studies with a relatively small number of patients that HBV itself did not affect the clinical outcomes of the COVID-19 after adjusting for comorbidities. 9 11 18 …”
Section: Discussionmentioning
confidence: 99%
“… 10 However, there are very few reports on the prognosis of COVID-19 in hepatitis B virus (HBV) carriers. 9 11 In addition, there are no reports on whether there is a difference in the prognosis of patients undergoing treatment for HBV. Although many studies are underway to develop a treatment for COVID-19, no treatment has been proven effective yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 23 However, it is unclear how infection with HBV influences the risk of SARS-CoV-2 infection; few studies have suggested a lower risk of infection for persons with chronic HBV infection prompting speculation on the possibility of ‘immune exhaustion’ as a result of long standing infection with HBV. 23 24 However, these studies were from the early phases of the pandemic in 2020. Given the constant evolution of the variants, further investigations to study the relationship between COVID-19 and chronic HBV are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have indicated that some COVID-19 patients have an abnormal liver function; e.g., the American College of Gastroenterology reported that approximately 20%-30% of patients had elevated liver enzymes, and another study from China suggested that 50.7% of SARS-CoV-2-infected patients had liver abnormalities ( 371 ). Of note, elevated liver function results were reported to be associated with moderate-high degree fever and lower T cell function (both CD4 + and CD8 + T cells) ( 371 ), and patients with preexisting liver disease (such as hepatitis B infection) carry a higher risk of developing severe disease ( 372 , 373 ).…”
Section: Clinical Symptomsmentioning
confidence: 99%